France Chartres 17th-c-engraving - Auteur inconnu (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: France Chartres 17th-c-engraving. Seventeenth-century engraving of Chartres's skyline.
Licence Public domain via Wikimedia Commons
Keywords: iconographie; illustration; gravure; Patrimoine; Wikimedia Commons